2021
DOI: 10.1111/exd.14386
|View full text |Cite
|
Sign up to set email alerts
|

Optoacoustic imaging of the skin

Abstract: Optoacoustic (OA, photoacoustic) imaging capitalizes on the synergistic combination of light excitation and ultrasound detection to empower biological and clinical investigations with rich optical contrast while effectively bridging the gap between micro and macroscopic imaging realms. State-of-the-art OA embodiments consistently provide images at micron-scale resolution through superficial tissue layers by means of focused illumination that can be smoothly exchanged for acoustic-resolution images at diffuse l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 156 publications
(181 reference statements)
0
33
0
3
Order By: Relevance
“…Figure 3A shows the experimental result about diameters of the optical and acoustic focal spots as functions of the applied voltage. As the applied voltage is increased, the interface deformities of two immiscible liquids become more obvious so that the radius of curvature of the interface is decreasing, which eventually causes the focal length to decrease, according to Equation (1). Owing to the performance of varifocal lens is affected by the f-number, the resolution of 3D-CPAD can be changed as the variation of confocus.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 3A shows the experimental result about diameters of the optical and acoustic focal spots as functions of the applied voltage. As the applied voltage is increased, the interface deformities of two immiscible liquids become more obvious so that the radius of curvature of the interface is decreasing, which eventually causes the focal length to decrease, according to Equation (1). Owing to the performance of varifocal lens is affected by the f-number, the resolution of 3D-CPAD can be changed as the variation of confocus.…”
Section: Resultsmentioning
confidence: 99%
“…Photoacoustic dermoscopy (PAD), an important embranchment of optical absorption-based photoacoustic microscopy (PAM), can be used to acquire highspatial-resolution imaging of skin tissue with high contrast based on its strong optical absorption and deep acoustic penetration [1][2][3] and allow functional and structural information via the visualization of skin structures in vivo [4,5]. Over the recent years, lots of integrated PADs have been developed for the diagnosis of skin diseases such as melanoma [6,7], port-wine stains [8,9], psoriasis [10], café au lait spots [11], pigmented nevus [12], scar [13] and human cuticle microvasculature [14,15] imaging.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a salivary gland stimulation challenge conducted in mouse models, a decrease in sO 2 change between measurements taken before and after salivary stimulation post-EBRT was associated with radiation-induced salivary gland toxicity in a murine model assessed with macroscopic PAI ( Figure 1B ) ( 60 ). Mesoscopic implementations of PAI can achieve ~20 μm in-plane resolution up to ~3 mm in depth for skin imaging ( 52 , 127 ), indicating potential for clinical skin toxicity assessment ( 128 ). Preliminary work on skin atopic dermatitis grading ( 61 ) showed that combining PAI mesoscopy-derived total blood volume, average vessel diameter, and ratio of low to high frequency signals gave a discriminating signature for atopic skin dermatitis grade ( Figure 1C ) ( 129 ).…”
Section: Potential Uses Of Photoacoustic Imaging In Radiotherapymentioning
confidence: 99%
“…It has greatly reduced the effect of tissue scattering of photons using one-way ultrasound detection while retaining a high optical absorption contrast (16)(17)(18)(19)(20)(21)(22)(23). Successful use of PAM has been reported in numerous studies (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), including observations of cell distribution, monitoring of vascularization, and label-free photoacoustic (PA) angiography. However, the opto-sono objective in most PAM setups is insufficient for clinical use in dermatology given its single-scale mode (single magnification or depth of focus), which results in a poor depth of resolution and a low signal-to-noise ratio (SNR).…”
Section: Introductionmentioning
confidence: 99%